Caring and sharing : the cultural heritage environment as an agent for change : 2016 ALECTOR Conference, Istanbul, Turkey /: the cultural heritage environment as an agent for change : 2016 ALECTOR Conference, Istanbul, Turkey. ([2018]) - Unknown
No abstract available